Chronicle of the European case law on equality (from 1/9/2021 to 31/8/2022) - Jacqmain, Jean (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
This paper deals with the analysis of judgments related to the principle of equal treatment and opportunities and delivered from September 1, 2021 until August 31, 2022 by the Court of Justice and General Court of the European Union and the European Court of Human Rights. It also covers the Judgments handed down by the Court of the European Free Trade Association (EFTA Court).